A very poorly expressed tRNA(Ser) is highly concentrated together with replication primer initiator tRNA(Met) in the yeast Ty1 virus-like particles. - Pochart, P (1993)
The analysis of the tRNAs associated to the virus-like particles produced by the Ty1 element revealed the specific packaging of three major tRNA species, in about equal amounts: the replication primer initiator tRNA(Met), the tRNA(Ser)AGA and a tRNA undetected until now as an expressed species in yeast. The latter tRNA is coded by the already described tDNA(Ser)GCT. This tRNA is enriched more than 150 fold in the particles as compared to its content in total cellular tRNA where it represents less than 0.1% (initiator tRNA(Met) and tRNA(Ser)AGA being 11 and 4 fold enriched respectively). This tRNA is the only species coded by the tDNA(Ser)GCT gene which is found in three copies per genome since no other corresponding expressed tRNA could be detected. This gene is thus very poorly expressed. The high concentration of tRNA(Ser)GCU in the particles compared to its very low cellular content led us to consider its possible implication in Ty specific processes.